2020
DOI: 10.1093/jisesa/ieaa013
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Ultrastructure of Antennal Sensilla of Adult Glenea cantor (Cerambycidae: Lamiinae)

Abstract: The external morphology and distribution of antennal sensilla of Glenea cantor Fabricius were studied with scanning electron microscopy. The antennae of G. cantor were observed to be filiform, consisting of scape, pedicel, and flagellum (nine flagellomeres). Four distinct types of sensory receptors were observed, including sensilla chaetica, sensilla trichodea, sensilla basiconica, and Böhm bristles. Three morphological subtypes of sensilla chaetica were found on the antennae, and sensilla trichodea were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 27 publications
4
28
0
Order By: Relevance
“…In the past half century, the antennal scanning electron microscopy of insects has been well-researched [ 23 25 ]. As phytophagous insects, Cerambycidae are economically important pests of forest, street trees and fruit trees [ 34 ]. Therefore, antenna scanning electron microscopy of cerambycid beetles has gained much recent research attention [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past half century, the antennal scanning electron microscopy of insects has been well-researched [ 23 25 ]. As phytophagous insects, Cerambycidae are economically important pests of forest, street trees and fruit trees [ 34 ]. Therefore, antenna scanning electron microscopy of cerambycid beetles has gained much recent research attention [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main reported functions for sensilla chaetica and Böhm bristles show a mechanical function [ 26 , 34 , 35 ]. Meanwhile, some research also have shown that several subtypes of sensilla chaetica have an olfactory function [ 34 ], such as SCh II & IV in A . asiaticus and C .…”
Section: Discussionmentioning
confidence: 99%
“…In May 2019, the G. cantor larvae were originally collected from Qingxiu Mountain (22°47′ N, 108°23′ E) in Nanning City, Guangxi Province, China by cutting down damaged kapok branches. The branches were kept in cages for adult eclosion, and then the insects were reared, as introduced previously [ 3 ]. The insects were reared with ventilation under 25 ± 1 °C, 75 ± 5% relative humidity (RH), and a photoperiod of 14:10 [L:D] h.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in 2005, this pest killed over 10% of the trees in a B. ceiba plantation in Nanning, Guangxi Province, China [ 1 ]. In 2018, B. ceiba was discovered as a new important host plant for long-horned beetles in Nanning, Guangxi Province [ 3 ]. In severe cases, it often causes the kapok trees to die continuously, which seriously affects the results of urban greening and landscaping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation